(untitled) (International journal of medical sciences, 2026)
This article analyzes the pedagogy of working with technical school students, modern approaches to organizing effective education, and the impact of interactive methods on educational quality. The research findings demonstrate the contribution of effective pedagogical organization to improving the professional training of technical school students.